Polymer matrix for electroplating and method for its preparation
Patent Information
- Application Number
- CN202580020656.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-14
- Filing Date
- 2025-03-14
- Publication Date
- 2026-10-27
Smart Images

Figure CN122996233A_ABST
Abstract
Description
[0001] Priority requirements
[0002] This application claims the benefit of U.S. Provisional Patent Application No. 63 / 565,426 (Attorney General’s Case No. 1202407), filed March 14, 2024, the contents of which are incorporated herein by reference in their entirety. Technical Field
[0003] This invention relates to polymer matrices, and more particularly to polymer matrices suitable for electroplating applications. Background Technology
[0004] Acrylonitrile-butadiene-styrene (ABS) is used in a variety of injection molding applications, including bath and hygiene products and product packaging. The ABS matrix also provides a good surface for electroplating, allowing the matrix to be coated with a metal layer. However, with increasingly stringent regulations on styrene-containing materials, there is a desire for styrene-free alternatives that offer a suitable surface for electroplating. Additionally, if the alternative materials have different shrinkage rates, manufacturers may need to create new molds for each part to accommodate the new material.
[0005] Therefore, there is still a need for alternative polymer matrices that have a similar shrinkage rate to ABS and provide a surface suitable for electroplating. Summary of the Invention
[0006] The following is a brief overview of the topics discussed in more detail herein. However, this overview is not intended to limit the scope of the claims.
[0007] According to a first aspect of the invention, a method for depositing metal on a polymer matrix includes providing a polymer matrix and depositing one or more metal layers on its surface. The polymer matrix has one or more surfaces made of a polymer composition comprising a polyolefin polymer, a cyclic olefin copolymer, and an inorganic filler. The method may be an electroplating method. In any aspect, the method may further include preparing one or more surfaces by creating a porous surface through pore forming, wherein one or more metal layers are deposited on the porous surface.
[0008] The one or more metal layers may be selected from palladium, nickel, and copper. The average particle size of the inorganic filler may be about 2-5 micrometers. In some aspects, the inorganic filler includes calcium carbonate.
[0009] In some aspects, the inorganic filler further includes needle-like fillers. The needle-like fillers may include wollastonite. The aspect ratio of the needle-like fillers may be greater than 1:5. In some aspects of the invention, the inorganic filler may contain greater than 0 to about 15 wt% needle-like fillers based on the total weight of the polymer matrix. The needle-like fillers may be silanized. In some aspects of the invention, the polymer matrix may be substantially free of styrene-containing polymers.
[0010] In various aspects, a polymer article includes one or more outer surfaces made of a polymer composition and a metallic coating deposited on said one or more outer surfaces. The polymer composition includes a polyolefin polymer, a cyclic olefin copolymer, and an inorganic filler. In some aspects, the polyolefin polymer includes a polypropylene polymer. The polypropylene polymer may be a homopolymer of propylene or a copolymer of propylene with one or more olefin monomers.
[0011] In some aspects of the invention, the inorganic filler comprises a first inorganic filler and a second inorganic filler, wherein the second inorganic filler is a needle-like filler. The average particle size of the first inorganic filler may be about 2-5 micrometers. The inorganic filler may contain more than 0 to about 15 wt% needle-like filler by weight of the total polymer composition. The needle-like filler may be silanized. The aspect ratio of the needle-like filler may be greater than 1:5. In any aspect, when measured by image analysis, the length D90 of the needle-like filler may be about 25-150 μm. The needle-like filler may be wollastonite. In some aspects, the inorganic filler further comprises at least one additional filler selected from: talc, barium sulfate, calcined kaolin, mica, carbon black, metal powder, graphite, and combinations thereof.
[0012] In various aspects, the polymer composition comprises a polyolefin polymer, a cyclic olefin copolymer, and an inorganic filler including a first inorganic filler and a second inorganic filler, wherein the second inorganic filler is needle-shaped. The aspect ratio of the calcium carbonate can be less than 1:5. In some aspects, at least one additional inorganic filler comprises needle-shaped wollastonite. When measured by image analysis, the length D90 of the needle-shaped wollastonite can be about 25-150 μm. The needle-shaped wollastonite can be silanized. In some aspects, the wollastonite can be treated with aminosilane.
[0013] In any aspect, the polymer composition may contain about 0.1-15 wt% acicular wollastonite based on the total weight of the polymer composition. The cyclic olefin copolymer may be an ethylene-norbornene copolymer. The polyolefin polymer may be a polypropylene polymer. In some aspects, the polypropylene polymer is a propylene homopolymer or a copolymer of propylene with one or more olefin monomers.
[0014] In any aspect of this document, measured according to ISO 294 with the specimen geometry described in ISO 527-Type 1A, the polymer composition exhibits a shrinkage rate of about 0.4-0.8%. The polymer composition may contain about 33-63 wt% of a polyolefin polymer by weight. The polymer composition may contain about 2.5-40 wt% of a cyclic olefin copolymer by weight. The polymer composition may contain about 10-40 wt% of a first inorganic filler by weight. The first inorganic filler may be calcium carbonate.
[0015] The above overview is a simplified summary designed to provide a basic understanding of some aspects of the systems and / or methods discussed herein. This overview is not a comprehensive review of the systems and / or methods discussed herein. It is not intended to identify key / essential elements of the systems and / or methods, nor to indicate their scope. Its sole purpose is to present some concepts in a simplified form as an introduction to the more detailed description that follows. Attached Figure Description
[0016] The general inventive concept, its descriptive embodiments, and advantages are described in more detail below with reference to the accompanying drawings, wherein:
[0017] Figure 1 Example polymer articles comprising a polymer matrix and a metal layer, describing one or more aspects of the present invention;
[0018] Figure 2 Another example of a polymer article comprising a polymer matrix and multiple metal layers, which describes one or more aspects of the present article;
[0019] Figure 3A These are microscopic images of the polymer matrix of comparative example C2 described in this article;
[0020] Figure 3B This is another microscopic image of the polymer matrix of Comparative Example C2 described in this article;
[0021] Figure 3C These are microscopic images of the polymer product after electroplating of the polymer matrix of Comparative Example C2 described in this article;
[0022] Figure 3D This is another microscopic image of the polymer product after electroplating of the polymer matrix of Comparative Example C2 described in this article;
[0023] Figure 4A These are microscopic images of the polymer matrix of Example E1 described herein;
[0024] Figure 4BThis is another microscopic image of the polymer matrix of Example E1 described herein;
[0025] Figure 4C These are photographs of the polymer matrix of Example E1 described herein before electroplating (right side of the image) and after electroplating (left side of the image);
[0026] Figure 5A These are microscopic images of the polymer matrix of Example E2 described herein;
[0027] Figure 5B These are microscopic images of the polymer matrix of Example E2 described herein;
[0028] Figure 5C These are photographs of the polymer matrix of Example E2 described herein before electroplating (left side of the image) and after electroplating (right side of the image);
[0029] Figure 6A These are microscopic images of the polymer matrix of Example E4 described herein;
[0030] Figure 6B These are microscopic images of the polymer matrix after electroplating in Example E4 described herein;
[0031] Figure 7A These are microscopic images of the polymer matrix of Example E5 described herein; and
[0032] Figure 7B These are microscopic images of the polymer matrix after electroplating in Example E5 described herein. Detailed Implementation
[0033] This document discloses polymer compositions comprising polyolefins, cyclic olefin copolymers, and inorganic fillers; articles made from said polymer compositions; and methods for depositing metal thereon. The polymer compositions offer advantages over conventional materials by providing high surface quality and low shrinkage. Specifically, in all aspects described herein, polymer articles can be formed from said polymer compositions using injection molding techniques while maintaining properties similar to ABS, such as shrinkage, allowing manufacturers to continue using existing molds. The polymer articles also have surfaces suitable for electroplating. Other advantages are also possible and anticipated, and can be realized based on the following disclosures.
[0034] The terminology used herein is for descriptive purposes only and should not be construed as limiting the entire invention. Unless otherwise specified in the relevant context or expressly implied otherwise, all references to the singular features or limitations of the invention should include the corresponding plural features or limitations, and vice versa. Unless otherwise indicated, “an” and “at least one” are used interchangeably. Furthermore, as applied in the specification and appended claims, unless the context expressly indicates otherwise, articles in the singular form include their plural forms.
[0035] Unless otherwise expressly defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art.
[0036] Unless otherwise expressly stated, no method disclosed herein should be construed as requiring its steps to be performed in a particular order, nor should any article described herein be construed as requiring a particular order or orientation of its components.
[0037] When the term "comprising" is used in this specification or claims, it is inclusive in a manner similar to "including," just as it is interpreted when used as a transitional word in the claims. Similarly, when the term "or" (e.g., A or B) is used, it means "A or B or both." The term "A or B only, and not both" is used when the applicant intends to mean "only A or B, and not both." Therefore, the term "or" is used herein in an inclusive, not exclusive, manner.
[0038] Any composition described in this invention may comprise or consist substantially of the essential elements of the invention described herein, as well as any additional or optional elements described herein or elements that are additionally useful in injection molding and / or electroplating applications.
[0039] Unless otherwise stated, all percentages, parts and ratios used herein are by weight of the “dry” total mixture, i.e., solvent-free.
[0040] All ranges and parameters disclosed herein, including but not limited to percentages, parts, and ratios, should be understood to include any and all subranges given and contained therein, as well as every numerical value between the endpoints. For example, the range “1-10” should be considered to include any and all subranges (e.g., 1-6.1 or 2.3-9.4) that begin with a minimum value of 1 or greater and end with a maximum value of 10 or less, as well as every integer contained within the range (1, 2, 3, 4, 5, 6, 7, 8, 9, and 10). A range may be expressed herein as from “about” one particular value and / or to “about” another particular value. When such a range is expressed, other embodiments include from one particular value and / or to another particular value. Similarly, when a value is expressed as an approximation using the antecedent “about”, it should be understood that the particular value forms another embodiment. It should be further understood that the endpoints of each range are meaningful relative to one endpoint, but independent of the other endpoint.
[0041] As stated herein, unless otherwise specified, the term "wt%" refers to the weight fraction of a single component based on the total weight of the thermoplastic layer composition.
[0042] Additionally, as used herein, the term “exemplary” means used as a description or instance of something, and not as a preference.
[0043] As used in this article, the term "polymer" includes homopolymers, copolymers, terpolymers, and mixtures thereof.
[0044] In all the aspects provided herein, a polymer article is disclosed comprising a polymer matrix made of a polymer composition and a metallic coating deposited on the polymer matrix. Figure 1 As shown, in any aspect described herein, the polymer article 100 may include a plurality of polymer matrices 102 and a metal layer 104. The outer surface of the polymer matrix 102 is in contact with the metal layer 104. In any aspect described herein, the polymer composition may comprise a polyolefin polymer, a cyclic olefin copolymer, and an inorganic filler. The polymer matrix may exhibit shrinkage values similar to ABS and properties suitable for electroplating. Depending on the specific aspect, other advantages may be achieved, which will be described in more detail below.
[0045] polymer matrix
[0046] As described above, the polymer matrix 102 may include polyolefin polymers, cyclic olefin copolymers, and inorganic fillers. These components may be compounded together and extruded or injection molded to form a polymer matrix well-suited for electroplating applications.
[0047] Polyolefin polymers
[0048] Polymer matrix 102 is formed from a composition comprising a polyolefin polymer (such as semi-crystalline polypropylene). In all aspects provided herein, the polyolefin polymer may include a polypropylene polymer. The polypropylene polymer may be, for example, a homopolymer of propylene or a copolymer of propylene with one or more olefin monomers. The term "homogeneous polymer" refers to a polymer made by linking olefin monomers without a comonomer (e.g., polymerizing a single type of monomer). As used herein, the term "comonomer" refers to an olefin comonomer suitable for polymerization with olefin monomers, such as an ethylene monomer (in the case of ethylene polymers) or a propylene monomer (in the case of propylene polymers). Comonomers may include, for example, but not limited to, linear or branched aliphatic C3-C... 20α-Olefins, such as propylene, 1-butene, 1-pentene, 3-methyl-1-butene, 4-methyl-1-pentene, 3-methyl-1-pentene, 1-hexene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, and 1-eicosene. Suitable commercially available polyolefins include those sold under the trade name DUPURE®, including DUPURE® U76 and DUPURE® Y76 (Ducor Petrochemicals).
[0049] When measured at 2.16 kg and 230 °C, the melt flow index (MFI) of the polypropylene polymer contained in the composition can be about 5-125 g / 10 min. For example, when measured at 2.16 kg and 230 °C, the MFI of the polypropylene polymer can be about 5-125 g / 10 min, about 10-100 g / 10 min, or about 25-75 g / 10 min. However, in some applications, polypropylene polymers with an MFI greater than about 125 g / 10 min or even less than about 5 g / 10 min may also be used.
[0050] In any aspect described herein, polyolefins may include recycled or regenerated polyolefins. For example, some or all of the polyolefin may be recycled or regenerated. In some aspects, the polyolefin may be a blend of recycled or regenerated polyolefins and virgin polyolefins, and may be entirely recycled or regenerated polyolefins or entirely virgin polyolefins.
[0051] In any aspect described herein, the content of polyolefin in the polymer composition, by weight of the total polymer composition, is at least about 25 wt%. The content of polyolefin in the polymer composition, by weight of the total polymer composition, may be greater than or equal to about 25 wt%, greater than or equal to about 28 wt%, greater than or equal to about 30 wt%, greater than or equal to about 33 wt%, greater than or equal to about 35 wt%, greater than or equal to about 38 wt%, greater than or equal to about 40 wt%, greater than or equal to about 45 wt%, or even greater than or equal to about 50 wt%, including any and all ranges and subranges encompassing any of these endpoints. In any aspect, the content of polyolefin in the polymer composition, by weight of the total polymer composition, may be less than or equal to about 65 wt%, less than or equal to about 63 wt%, less than or equal to about 60 wt%, less than or equal to about 55 wt%, less than or equal to about 50 wt%, less than or equal to about 45 wt%, less than or equal to about 40 wt%, or even less than or equal to about 35 wt%. For example, based on the total weight of the polymer composition, the polymer composition may contain the following amounts of polyolefin: about 25-65 wt%, about 28-65 wt%, about 30-65 wt%, about 33-65 wt%, about 35-65 wt%, about 38-65 wt%, about 40-65 wt%, about 45-65 wt%, about 50-65 wt%, about 25-63 wt%, about 28-63 wt%, about 30-63 wt%, about 33-63 wt%, about 35-63 wt%, about 38-63 wt%, about 40-63 wt%, about 45-63 wt%, about 50-63 wt%, about 25-60 wt%, about 28-60 wt%, about 30-60 wt%, about 33-60 wt%, about 35-60 wt%, about 38-60 wt%, about 40-60 wt%. wt%, approximately 45-60 wt%, approximately 50-60 wt%, approximately 25-55 wt%, approximately 28-55 wt%, approximately 30-55 wt%, approximately 33-55 wt%, approximately 35-55 wt%, approximately 38-55 wt%, approximately 40-55 wt%, approximately 45-55 wt%, approximately 50-55 wt%, approximately 25-50 wt%, approximately 28-50 wt%, approximately 30-50 wt%, approximately 33-50 wt%, approximately 35-50 wt%, approximately 38-50 wt%, approximately 40-50 wt%, approximately 45-50 wt%, approximately 25-45 wt%, approximately 28-45 wt%, approximately 30-45 wt%, approximately 33-45 wt%, approximately 35-45 wt%, approximately 38-45 wt%, or even approximately 40-45 wt%, including any and all ranges and subranges that contain any of these endpoints.
[0052] While other amounts of polyolefins are possible and anticipated, increasing the amount of polyolefins in the composition may result in a shrinkage rate greater than that of conventional ABS compositions. Therefore, although such polymer compositions containing more polyolefins may provide surfaces suitable for electroplating, injection molding processes previously using conventional ABS compositions may require new molds.
[0053] cyclic olefin copolymers
[0054] The polymer composition forming polymer matrix 102 also includes a cyclic olefin copolymer (COC). In all respects described herein, the COC is a copolymer produced by chain polymerization of a cyclic monomer with an olefin monomer. For example, the cyclic monomer may be 8,9,10-trinorbornene-2-ene (norbornene) or 1,2,3,4,4a,5,8,8a-octahydro-1,4:5,8-dimethylbridged naphthalene (tetracyclododecene). The olefin monomer in the COC may be, for example, ethylene or propylene. The COC may be an ethylene-norbornene copolymer. Commercially available COCs suitable for the application include those marketed under the trade name TOPAS. TM Those for sale, including TOPAS TM 5013L-10 and TOPAS TM 5013S-04 (both from TOPAS Advanced Polymers). In all respects described herein, COC is an amorphous polymer. It is believed that the addition of an amorphous polymer to a polymer composition can reduce the shrinkage rate of the polymer composition because it weakens the orderliness of the polymer matrix imparted by the semi-crystalline polyolefin.
[0055] In any aspect described herein, the content of COC in the polymer composition is at least about 2.5 wt% based on the total weight of the polymer composition. The content of COC in the polymer composition may be greater than or equal to about 2.5 wt%, greater than or equal to about 5 wt%, greater than or equal to about 7.5 wt%, greater than or equal to about 10 wt%, greater than or equal to about 15 wt%, greater than or equal to about 20 wt%, greater than or equal to about 25 wt%, or even greater than or equal to about 30 wt% based on the total weight of the polymer composition, including any and all ranges and subranges encompassing any of these endpoints. In any aspect, the content of COC in the polymer composition may be less than or equal to about 40 wt%, less than or equal to about 35 wt%, less than or equal to about 30 wt%, less than or equal to about 25 wt%, less than or equal to about 20 wt%, less than or equal to about 15 wt%, less than or equal to about 12 wt%, or even less than or equal to about 10 wt% based on the total weight of the polymer composition. For example, based on the total weight of the polymer composition, the polymer composition may contain the following amounts of COC: about 2.5-40 wt%, about 5-40 wt%, about 7.5-40 wt%, about 10-40 wt%, about 15-40 wt%, about 20-40 wt%, about 25-40 wt%, about 30-40 wt%, about 2.5-35 wt%, about 5-35 wt%, about 7.5-35 wt%, about 10-35 wt%, about 15-35 wt%, about 20-35 wt%, about 25-35 wt%, about 30-35 wt%, about 2.5-30 wt%, about 5-30 wt%, about 7.5-30 wt%, about 10-30 wt%, about 15-30 wt%, about 20-30 wt%, about 25-30 wt%, about 2.5-25 wt%, about 5-25 wt%. wt%, about 7.5-25 wt%, about 10-25 wt%, about 15-25 wt%, about 20-25 wt%, about 2.5-20 wt%, about 5-20 wt%, about 7.5-20 wt%, about 10-20 wt%, about 15-20 wt%, about 2.5-15 wt%, about 5-15 wt%, about 7.5-15 wt%, about 10-15 wt%, about 2.5-10 wt%, about 5-10 wt%, or even about 7.5-10 wt%, including any and all ranges and subranges containing any of these endpoints.
[0056] filler components
[0057] The polymer composition also contains inorganic fillers. In various respects, the inorganic fillers reduce the shrinkage rate of the polymer composition to levels approaching those of unfilled ABS polymer compositions typically used in electroplating applications.
[0058] The inorganic filler particles may include any kind of ground inorganic particulate matter, such as ceramic fillers, glass beads, glass fibers, talc, barium sulfate, carbon black, metal powders, graphite, wollastonite, ground limestone, dolomite or silica, sand, cellulose materials, calcium carbonate, carbon, clay, perlite, mica, fumed silica, and combinations thereof. Other fillers commonly used in polymer compositions are possible and foreseeable.
[0059] In various aspects, the average particle size of the inorganic filler is less than or equal to about 5.0 μm. For example, the average particle size of the inorganic filler may be less than or equal to about 5.0 μm, less than or equal to about 4.5 μm, less than or equal to about 4.0 μm, less than or equal to about 3.5 μm, less than or equal to about 3.0 μm, or less than or equal to about 2.5 μm. The average particle size of the inorganic filler may be greater than or equal to about 2.0 μm. For example, the average particle size of the inorganic filler may be greater than or equal to about 2.0 μm, greater than or equal to about 2.5 μm, greater than or equal to about 3.0 μm, greater than or equal to about 3.5 μm, greater than or equal to about 4.0 μm, or greater than or equal to about 4.5 μm. In some aspects described herein, the average particle size of the inorganic filler may be about 2.0-5.0 μm. For example, the average particle size of the inorganic filler can be about 2.0-5.0 μm, about 2.5-5.0 μm, about 3.0-5.0 μm, about 3.5-5.0 μm, about 4.0-5.0 μm, about 4.5-5.0 μm, about 2.0-4.5 μm, about 2.5-4.5 μm, about 3.0-4.5 μm, about 3.5-4.5 μm, about 4.0-4.5 μm, about 2.0-4.0 μm, about 2.5-4.0 μm, about 3.0-4.0 μm, about 3.5-4.0 μm, about 2.0-3.5 μm, about 2.5-3.5 μm, about 3.0-3.5 μm, about 2.0-3.0 μm, or even about 2.0-2.5 μm. μm, including any and all ranges and subranges containing any of these endpoints. While other average particle sizes are expected and possible, smaller average particle sizes are believed to provide improved surface quality compared to compositions containing inorganic fillers with larger average particle sizes.
[0060] The content of inorganic filler in the polymer composition may be greater than or equal to about 10 wt% based on the total weight of the polymer composition. For example, the content of inorganic filler may be greater than or equal to about 10 wt%, greater than or equal to about 15 wt%, greater than or equal to about 20 wt%, greater than or equal to about 25 wt%, greater than or equal to about 30 wt%, or even greater than or equal to 35 wt%. The amount of inorganic filler in each aspect may be less than or equal to about 40 wt% based on the total weight of the polymer composition. For example, the content of inorganic filler in the polymer composition may be less than or equal to about 40 wt%, less than or equal to about 35 wt%, less than or equal to about 30 wt%, less than or equal to about 25 wt%, less than or equal to about 20 wt%, or less than or equal to about 15 wt%. According to one or more aspects, the content of inorganic filler in the polymer composition, based on the total weight of the polymer composition, may be about 10-40 wt%, about 15-40 wt%, about 20-40 wt%, about 25-40 wt%, about 30-40 wt%, about 35-40 wt%, about 10-35 wt%, about 15-35 wt%, about 20-35 wt%, about 25-35 wt%, about 30-35 wt%, about 10-30 wt%, about 15-30 wt%, about 20-30 wt%, about 25-30 wt%, about 10-25 wt%, about 15-25 wt%, about 20-25 wt%, about 10-20 wt%, about 15-20 wt%, or even about 10-15 wt%, including any and all ranges and subranges containing any of these endpoints.
[0061] In any aspect disclosed herein, inorganic fillers may comprise blends of two or more inorganic fillers (e.g., a first inorganic filler and a second inorganic filler). In any aspect described herein, polymer compositions may comprise a first inorganic filler and a second inorganic filler, wherein the second inorganic filler may be a needle-shaped filler. For example, polymer compositions may comprise a first inorganic filler and a second inorganic filler, wherein the first inorganic filler may be calcium carbonate and the second inorganic filler may be a needle-shaped filler.
[0062] Needle packing can be inorganic packing with an aspect ratio greater than or equal to 1:5. For example, the aspect ratio of needle packing can be greater than or equal to 1:5, greater than or equal to 1:8, greater than or equal to 1:10, greater than or equal to 1:15, greater than or equal to 1:20, greater than or equal to 1:25, or even greater than or equal to 1:30.
[0063] When measured using image analysis, the length D90 of the needle-like packing can be greater than or equal to about 25 μm. For example, the length D90 of the needle-like packing can be greater than or equal to about 25 μm, greater than or equal to about 30 μm, greater than or equal to about 35 μm, greater than or equal to about 40 μm, greater than or equal to about 45 μm, greater than or equal to about 50 μm, greater than or equal to about 60 μm, greater than or equal to about 70 μm, greater than or equal to about 80 μm, greater than or equal to about 90 μm, greater than or equal to about 100 μm, greater than or equal to about 110 μm, or even greater than or equal to about 120 μm. In some aspects, the length D90 of the needle-like packing is less than or equal to about 150 μm. For example, the length D90 of the needle-like packing may be less than or equal to about 150 μm, less than or equal to about 140 μm, less than or equal to about 130 μm, less than or equal to about 120 μm, less than or equal to about 110 μm, less than or equal to about 100 μm, less than or equal to about 80 μm, less than or equal to about 60 μm, or less than or equal to about 50 μm. The length D90 of the needle-like filler can be about 25-150 μm, about 50-150 μm, about 75-150 μm, about 100-150 μm, about 125-150 μm, about 25-125 μm, about 50-125 μm, about 75-125 μm, about 100-125 μm, about 25-100 μm, about 50-100 μm, about 75-100 μm, 25-about 75 μm, about 50-75 μm, or about 25-50 μm, including any and all ranges and subranges that include any of these endpoints.
[0064] The needle-shaped filler is surface-treated in any one or more ways. For example, the needle-shaped filler can be treated with aminosilane. Treating the needle-shaped filler with aminosilane can provide improved properties, such as mechanical properties, compatibility with polymers in polymer compositions, and enhanced filling effect. In some aspects, the needle-shaped filler is wollastonite treated with aminosilane. In some aspects, the needle-shaped filler is silanized wollastonite.
[0065] When present, the needle-like filler content in the polymer composition is greater than 0 to about 15 wt% based on the total weight of the polymer composition. For example, the polymer composition may contain the following amounts of needle-like filler based on the total weight of the polymer composition: greater than 0 wt% to about 15 wt%, about 0.1-15 wt%, about 1-15 wt%, about 5-15 wt%, about 7.5-15 wt%, about 10-15 wt%, about 12.5-15 wt%, greater than 0 to about 12.5 wt%, about 0.1-12.5 wt%, about 1-12.5 wt%, about 5-12.5 wt%, about 7.5-12.5 wt%, or about 10-12.5 wt%, including any and all ranges and subranges containing any of these endpoints. It should be noted that the needle-like filler is optional, and therefore the polymer composition may not contain needle-like filler. Furthermore, while the specific content of needle-like filler in the polymer composition may vary, increasing the amount of needle-like filler may adversely affect surface quality, making the polymer matrix unsuitable for electroplating applications. In any respect described herein, the needle-like filler may be needle-like wollastonite.
[0066] In some aspects of the invention, the inorganic filler is a blend of calcium carbonate and needle-like filler. For example, the inorganic filler may include a first inorganic filler comprising calcium carbonate and a second inorganic filler comprising needle-like wollastonite.
[0067] Calcium carbonate is commercially available from various sources. In all respects, the average particle size of calcium carbonate is less than or equal to about 5.0 μm. For example, the average particle size of calcium carbonate can be less than or equal to about 5.0 μm, less than or equal to about 4.5 μm, less than or equal to about 4.0 μm, less than or equal to about 3.5 μm, less than or equal to about 3.0 μm, or less than or equal to about 2.5 μm. The average particle size of calcium carbonate can also be greater than or equal to about 2.0 μm. For example, the average particle size of calcium carbonate can be greater than or equal to about 2.0 μm, greater than or equal to about 2.5 μm, greater than or equal to about 3.0 μm, greater than or equal to about 3.5 μm, greater than or equal to about 4.0 μm, or greater than or equal to about 4.5 μm. In all respects described herein, the average particle size of calcium carbonate can be from about 2.0 to 5.0 μm. For example, the average particle size of calcium carbonate can be approximately 2.0–5.0 μm, approximately 2.5–5.0 μm, approximately 3.0–5.0 μm, approximately 3.5–5.0 μm, approximately 4.0–5.0 μm, approximately 4.5–5.0 μm, approximately 2.0–4.5 μm, approximately 2.5–4.5 μm, approximately 3.0–4.5 μm, approximately 3.5–4.5 μm, approximately 4.0–4.5 μm, approximately 2.0–4.0 μm, approximately 2.5–4.0 μm, approximately 3.0–4.0 μm, approximately 3.5–4.0 μm, approximately 2.0–3.5 μm, approximately 2.5–3.5 μm, approximately 3.0–3.5 μm, approximately 2.0–3.0 μm, approximately 2.5–3.0 μm, or even approximately 2.0–2.5 μm. μm, including any and all ranges and subranges containing any of these endpoints. While other average particle sizes are expected and possible, it is believed that smaller average particle sizes provide improved surface quality compared to compositions containing calcium carbonate with larger average particle sizes.
[0068] In various respects, calcium carbonate has an aspect ratio of less than 1:5. As used herein, aspect ratio refers to the ratio of the major axis (length) to the minor axis (width) of the ellipse fitted to the particle shape. For example, the aspect ratio of calcium carbonate can be less than 1:5, less than 1:4.5, less than 1:4, less than 1:3.5, less than 1:3, less than 1:2.5, less than 1:2, less than 1:1.5, or even approximately 1:1. In some respects, calcium carbonate particles can be described as approximately spherical. In some respects, needle-like fillers have a greater aspect ratio than calcium carbonate.
[0069] The content of calcium carbonate in the polymer composition may be greater than or equal to about 10 wt% based on the total weight of the polymer composition. For example, the content of calcium carbonate may be greater than or equal to about 10 wt%, greater than or equal to about 15 wt%, greater than or equal to about 20 wt%, greater than or equal to about 25 wt%, greater than or equal to about 30 wt%, or even greater than or equal to 35 wt%. In various aspects, the content of calcium carbonate may be less than or equal to about 40 wt% based on the total weight of the polymer composition. For example, calcium carbonate may be included in the polymer composition in the following amounts: less than or equal to about 40 wt%, less than or equal to about 35 wt%, less than or equal to about 30 wt%, less than or equal to about 25 wt%, less than or equal to about 20 wt%, or less than or equal to about 15 wt%. According to any one or more aspects, calcium carbonate may be included in the polymer composition in the following amounts based on the total weight of the polymer composition: about 10-40 wt%, about 15-40 wt%, about 20-40 wt%, about 25-40 wt%, about 30-40 wt%, about 35-40 wt%, about 10-35 wt%, about 15-35 wt%, about 20-35 wt%, about 25-35 wt%, about 30-35 wt%, about 10-30 wt%, about 15-30 wt%, about 20-30 wt%, about 25-30 wt%, about 10-25 wt%, about 15-25 wt%, about 20-25 wt%, about 10-20 wt%, about 15-20 wt%, or even about 10-15 wt%, including any and all ranges and subranges containing any of these endpoints.
[0070] additive
[0071] In any aspect described herein, the polymer matrix 102 may also include one or more additives. In some aspects, the thermoplastic layer may include one or more additives selected from antioxidants, lubricants, light stabilizers, mold release agents, colorants, impact modifiers, toughening agents, and combinations thereof. Depending on the specific aspect and application, other additives may be added, such as flame retardants, reducing agents, crosslinking agents, adhesion modifiers, UV absorbers, whitening agents, etc. However, it should be understood that the addition of one or more additives is optional, and therefore the polymer matrix may not contain any additives.
[0072] When present, the amount of additive in the polymer composition is greater than 0 wt% to about 2 wt% based on the total weight of the polymer composition. For example, based on the total weight of the polymer composition, the total content of additives in the polymer composition can be greater than 0 wt% to about 2 wt%, greater than 0 wt% to about 1.5 wt%, greater than 0 wt% to about 1 wt%, greater than 0 wt% to about 0.75 wt%, greater than 0 wt% to about 0.5 wt%, greater than 0 wt% to about 0.25 wt%, about 0.05-2 wt%, about 0.05-1.5 wt%, about 0.05-1 wt%, about 0.05-0.75 wt%, about 0.05-0.5 wt%, about 0.05-0.25 wt%, about 0.1-2 wt%, about 0.1-1.5 wt%, about 0.1-1 wt%, about 0.1-0.75 wt%, about 0.1-0.5 wt%, about 0.1-0.25 wt%, about 0.15-2 wt%, about 0.15-1.5 wt%. wt%, about 0.15-1 wt%, about 0.15-0.75 wt%, about 0.15-0.5 wt%, about 0.15-0.25 wt%, about 0.2-2 wt%, about 0.2-1.5 wt%, about 0.2-1 wt%, about 0.2-0.75 wt%, or about 0.2-0.5 wt%, including any and all ranges and subranges containing any of these endpoints.
[0073] preparation
[0074] In any aspect described herein, the polymer matrix 102 can be formed by compounding or otherwise combining a polyolefin, COC, filler components, and optionally one or more additives to prepare a polymer composition. The polymer composition can be used to form the polymer matrix 102 by injection molding, extrusion, or any other suitable method for forming a polymer matrix. In some aspects, the specific method for preparing the polymer matrix can vary depending on the components contained in the polymer composition and the desired final properties of the polymer matrix. For example, injection molding can be used to prepare the polymer matrix.
[0075] In any aspect described herein, a polymer article may include one or more polymer matrices 102. For example, a polymer article may include one, two, three, four or more polymer matrices. Figure 1 The exemplary polymer article 100 shown herein includes a polymer matrix 102, but it should be understood that in any aspect described herein, one or more polymer matrices may be included.
[0076] Metal layer
[0077] As described above, the polymer article 100 further includes at least one metal layer 104. The metal layer 104 may be, for example, electrodeposited copper or rolled copper, nickel, palladium, gold, or other metals. In some aspects, the metal layer may undergo surface treatment to improve one or more properties, including heat resistance, weather resistance, etc. Other surface treatments may include surface roughening, silane coupling treatment, etc. In some aspects, the polymer article may undergo chromium-free treatment.
[0078] In any aspect provided herein, the thickness of the metal layer 104 may be about 1–500 μm, including about 1–250 μm, about 2.5–200 μm, about 3–100 μm, or even about 5–50 μm, including any and all ranges and subranges encompassing any of these endpoints. In some aspects, depending on the specific application, the thickness of the metal layer may be less than about 500 μm, less than about 200 μm, less than about 150 μm, less than about 100 μm, less than about 75 μm, less than about 50 μm, less than about 25 μm, or even less than about 10 μm.
[0079] In any aspect described herein, a polymer article may include one or more metal layers 104. For example, a polymer article may include one, two, three, four or more metal layers. Figure 1 The exemplary polymer article 100 shown includes three metal layers 104, but it should be understood that one or more metal layers may be included in any aspect described herein.
[0080] like Figure 2 As shown, in some aspects, metal layer 104 includes a palladium layer 106, a nickel layer 108, a copper layer 110, and a metal layer 112. Palladium layer 106 is deposited on the surface of polymer matrix 102, while nickel layer 108 is deposited on palladium layer 106, such that palladium layer 106 is located between the surface of polymer matrix 102 and nickel layer 108. Copper layer 110 is deposited on nickel layer 108, such that nickel layer 108 is located between palladium layer 106 and copper layer 110. Metal layer 112 is deposited on copper layer 110, such that copper layer 110 is located between metal layer 112 and nickel layer 108. The metal layer may, for example, include copper, zinc, tin, nickel, gold, silver, palladium, aluminum, chromium, or other metals and combinations thereof. Figure 2 The metal layers 104 are described in a specific order, but it should be understood that the order of the layers may vary depending on the specific aspect. Therefore, in some aspects, additional layers may be included in the polymer article 100.
[0081] Performance and products
[0082] As described above, in various aspects, the polymer matrix can be extruded or injection molded from a polymer composition with a shrinkage rate comparable to ABS. As stated herein, shrinkage is measured according to the specimen geometry described in ISO 527 - Type 1A, as per ISO 294. Shrinkage refers to the die shrinkage of the molded polymer material. In various aspects, the shrinkage rate of the polymer matrix is less than about 1%. For example, the shrinkage rate of the polymer matrix can be less than or equal to about 1.0%, less than or equal to about 0.9%, less than or equal to about 0.8%, less than or equal to about 0.7%, less than or equal to about 0.6%, or even less than or equal to about 0.5%. In any respect of this document, the shrinkage of the polymer matrix can be about 0.4-1.0%, about 0.4-0.9%, about 0.4-0.8%, about 0.4-0.7%, about 0.4-0.6%, about 0.4-0.5%, about 0.5-1.0%, about 0.5-0.9%, about 0.5-0.8%, about 0.5-0.7%, about 0.5-0.6%, about 0.6-1.0%, about 0.6-0.9%, about 0.6-0.8%, or even about 0.6-0.7%, including any and all ranges and subranges containing any of these endpoints.
[0083] In all respects, the polymer composition is substantially free of styrene-containing polymers or contains no styrene-containing polymers.
[0084] Preparation method
[0085] As described above, in any aspect described herein, the polymer matrix can be formed by compounding or otherwise combining a polyolefin, COC, filler components, and optionally one or more additives to prepare a polymer composition. The polymer composition can be formed by injection molding, extrusion, or any other suitable method for forming a polymer matrix. In each aspect, the polymer matrix is incorporated into a polymer article.
[0086] The metal layer 104 can be deposited on the polymer matrix 102 using any of the various techniques known and applied in the art. For example, the metal layer 104 can be deposited using electroplating, vacuum deposition, physical vapor deposition, electroless deposition, dip coating, chemical vapor deposition, etc. In any aspect disclosed herein, electroplating methods can be applied to deposit metal onto the polymer matrix 102.
[0087] Depending on the method used to deposit the metal layer 104 on the polymer matrix 102, additional processing may be required before or after metal deposition. For example, in some aspects, the polymer matrix can be prepared by creating a porous surface through pore formation on its surface, such as by chemical etching. The porous surface enables the metal layer to interlock with the polymer matrix 102.
[0088] In all respects disclosed, the polymer matrix exhibits electroplating properties similar to ABS. Therefore, the metal layer 104 can be deposited on the polymer matrix 102 using conventional electroplating methods for depositing metal layers on ABS matrices without requiring adjustments to the method itself (e.g., without changing the concentration or time of the electroplating material).
[0089] The general concept of the invention has been described above in general terms and with respect to various specific aspects. While the general inventive concept has been described and is believed to be exemplary, various alternatives will become apparent to those skilled in the art upon reading this disclosure. The general inventive concept is not limited except as set forth in the specific claims.
[0090] Example
[0091] The following examples are given for illustrative purposes only and do not limit the scope of the general inventive concepts described herein.
[0092] Six polymer matrices (E1-E6) and six comparative polymer matrices (C1-C6) were formed from the materials provided in Table 1 below.
[0093] Table 1
[0094]
[0095] Polyolefins, COC, and other materials are compounded in the amounts (wt%) provided in Table 2 to form polymer compositions. Each polymer composition is injected into a mold according to the revised ISO 294, wherein the plate size is different. Specifically, the test plate is not the test plate described in ISO 294-4 (60 x 60 x 2 mm), but is formed according to the specimen geometry described in ISO 527-Type 1A (a tensile bar with dimensions of 172 x 10 x 4 mm).
[0096] Measure density according to ISO 1183. Measure Charpy impact properties (e.g., notched and unnotched) at 23°C according to ISO 179 and record in Joules per meter (J / m) in Tables 2 and 3. Measure melt flow rate at 230°C and 2.16 kg according to ISO 1133 and report in g / 10 min in Tables 2 and 3. Measure shrinkage according to the revised ISO 294. The shrinkage rate of the ABS packaging measured using the revised ISO 294 is 0.5%.
[0097] Table 2
[0098]
[0099] The recorded value is the average of the values obtained from the two samples.
[0100] Table 3
[0101]
[0102] Each of Examples E1-E6 comprises a combination of polypropylene polymer and calcium carbonate inorganic filler, and these examples all show a shrinkage rate of less than 0.9, and in most cases less than 0.7. While Comparative Example C4 shows an excellent shrinkage rate (0.7), the resulting surface has a matte appearance, indicating that the addition of COC affected the surface quality. Similarly, Comparative Examples C1-C3 do not contain COC, but did not produce a surface quality suitable for electroplating, although their shrinkage rates were acceptable. Figures 3A-3D The polymer matrix of Comparative Example C2 before electroplating ( Figure 3A and 3B ) and after electroplating ( Figure 3C and 3D Microscopic images of the samples revealed surface defects. Additionally, comparative sample C3, containing glass fiber as a filler, exhibited good shrinkage, but surface pitting made it unsuitable for electroplating.
[0103] Comparative Examples C4 and C5 comprised similar amounts of inorganic filler as Examples E1 and E5, but excluded COC. As a result, the shrinkage rates of Comparative Examples C4 and C5 were greater than those of Examples E1 and E5, respectively. This indicates that COC also affects the shrinkage rate of the polymer composition.
[0104] from Figures 4A-4C and Figures 5A-5C As can be seen, the addition of COC improved the surface quality. Specifically, Figure 4A and 4B These are microscopic images of the polymer matrix of Example E1 before electroplating, and Figure 4C These are photographs of the polymer matrix of Example E1 before electroplating (right side of the image) and after electroplating (left side of the image). Figure 5A and 5B These are microscopic images of the polymer matrix of Example E2 before electroplating, and Figure 5C These are photographs of the polymer matrix of Example E2 before electroplating (left side of the image) and after electroplating (right side of the image). Figure 6A and 6B These are microscopic images of the polymer matrix of Example E4 before and after electroplating. Figure 7A and 7B These are microscopic images of the polymer matrix of Example E5 before and after electroplating. Figure 4A , 4B 5A, 5B, 6A, and 7A all indicate that the surface has no pitting and the overall appearance is glossy. Figure 4C , 5C Electroplated polymer products in grades 6B and 7B are glossy and free of defects, especially when compared with... Figure 3C and 3D Compared to the surface shown in the image.
[0105] Unless otherwise stated, every document cited herein is incorporated by reference in its entirety. No reference to any document should be construed as an admission of prior art to any invention disclosed or claimed herein. If any meaning or definition of a term in this document conflicts with the meaning or definition of the same term in any document incorporated by reference, the meaning or definition of that term as given in this document shall prevail.
[0106] It should be understood that various adjustments and changes can be made without departing from the scope of the invention as defined in the appended claims. More specifically, while some aspects of the invention are identified herein as preferred or particularly advantageous, it is contemplated that the invention is not limited to these aspects.
Claims
1. A method for depositing metal on a polymer matrix, comprising: A polymer matrix is provided, the polymer matrix having one or more surfaces made of a polymer composition comprising: Polyolefin polymers; cyclic olefin copolymers; and Inorganic fillers; and One or more metal layers are deposited on the surface.
2. The method of claim 1, wherein the one or more metal layers are selected from palladium, nickel, and copper.
3. The method of claim 1 or 2, wherein the average particle size of the inorganic filler is about 2-5 micrometers.
4. The method of any one of claims 3-4, wherein the inorganic filler comprises calcium carbonate.
5. The method of claim 3 or 4, wherein the inorganic filler further comprises needle-shaped filler.
6. The method of claim 5, wherein the needle-like filler comprises wollastonite.
7. The method of claim 5 or 6, wherein the length-to-diameter ratio of the needle-shaped packing is greater than 1:
5.
8. The method of any one of claims 5-7, wherein the inorganic filler comprises more than 0 wt% to about 15 wt% needle-like filler based on the total weight of the polymer matrix.
9. The method of any one of claims 5-8, wherein the needle-shaped filler is silanized.
10. The method of any of the preceding claims, wherein the polymer matrix is substantially free of styrene-containing polymers.
11. The method of any of the preceding claims, the method further comprising preparing one or more surfaces by forming a porous surface, wherein the one or more metal layers are deposited on the porous surface.
12. The method of any of the preceding claims, wherein the method is an electroplating method.
13. A polymer article comprising: One or more outer surfaces prepared from a polymer composition comprising: Polyolefin polymers; cyclic olefin copolymers; and Inorganic fillers; and A metallic coating deposited on one or more of the outer surfaces.
14. The polymer article of claim 13, wherein the polyolefin polymer comprises a polypropylene polymer.
15. The polymer article of claim 14, wherein the polypropylene polymer is a homopolymer of propylene or a copolymer of propylene with one or more olefin monomers.
16. The polymer article of any one of claims 13-15, wherein the inorganic filler comprises a first inorganic filler and a second inorganic filler, wherein the second inorganic filler is a needle-shaped filler.
17. The polymer article of claim 16, wherein the average particle size of the first inorganic filler is about 2-5 micrometers.
18. The polymer article of claim 16 or 17, wherein the needle-shaped filler is silanized.
19. The polymer article of any one of claims 16-18, wherein the aspect ratio of the needle-shaped filler is greater than 1:
5.
20. The polymer article of any one of claims 16-19, wherein the length D90 of the needle-like filler is about 25-150 μm when measured by image analysis.
21. The polymer article of any one of claims 16-20, wherein the needle-like filler is wollastonite.
22. The polymer article of any one of claims 16-21, wherein the inorganic filler further comprises at least one additional filler selected from: talc, barium sulfate, calcined kaolin, mica, carbon black, metal powder, graphite, and combinations thereof.
23. The polymer article of any one of claims 16-22, wherein the inorganic filler comprises more than 0 wt% to about 15 wt% needle-like filler based on the total weight of the polymer composition.
24. A polymer composition comprising: Polyolefin polymers; cyclic olefin copolymers; and Inorganic packing materials, including: First inorganic packing; and The second inorganic packing material is needle-shaped.
25. The polymer composition of claim 24, wherein the aspect ratio of the first inorganic filler is less than 1:
5.
26. The polymer composition of claim 24 or 25, wherein at least one additional inorganic filler comprises needle-shaped wollastonite.
27. The polymer composition of claim 26, wherein the length D90 of the acicular wollastonite is about 25-150 μm when measured by image analysis.
28. The polymer composition of claim 26 or 27, wherein the needle-like wollastonite is silanized.
29. The polymer composition of any one of claims 26-28, wherein the wollastonite is treated with an aminosilane.
30. The polymer composition of any one of claims 24-29, wherein the polymer composition comprises about 0.1-15 wt% acicular wollastonite based on the total weight of the polymer composition.
31. The polymer composition of any one of claims 24-30, wherein the cyclic olefin copolymer is an ethylene-norbornene copolymer.
32. The polymer composition of any one of claims 24-31, wherein the polyolefin polymer is a polypropylene polymer.
33. The polymer composition of claim 32, wherein the polypropylene polymer is a homopolymer of propylene or a copolymer of propylene with one or more olefin monomers.
34. The polymer composition of any one of claims 24-33, wherein the sample geometry described in ISO 527-Type 1A is measured according to ISO 294, and the polymer composition exhibits a shrinkage rate of about 0.4-0.8%.
35. The polymer composition of any one of claims 24-34, wherein the polymer composition comprises about 33-63 wt% of a polyolefin polymer based on the total weight of the polymer composition.
36. The polymer composition of any one of claims 24-35, wherein the polymer composition comprises about 2.5-40 wt% of a cyclic olefin copolymer based on the total weight of the polymer composition.
37. The polymer composition of any one of claims 24-36, wherein the polymer composition comprises about 10-40 wt% of a first inorganic filler based on the total weight of the polymer composition.
38. The polymer composition of any one of claims 24-37, wherein the first inorganic filler is calcium carbonate.
Citation Information
Patent Citations
Vehicle-spring.
US1202407A